Caregiver perspectives on TB-related stigma experienced by young children - L.S. Johnson; M.G. Anthony; C. Purdy; V. Luke; H. van Deventer; M. van Niekerk; L. Viljoen; M.M. van der Zalm; on behalf of the Umoya study team (IJTLD Open)
BACKGROUND: TB-related stigma often stems from a fear of TB infection, power dynamics between social groups, and an association of TB with socially undesirable traits. METHODS: This study was conducted in South Africa within a prospective observational TB diagnostic cohort study, ‘Umoya.’ StopTB stigma questionnaires and activity-based interviews were administered to caregivers of children aged 0–9 years with presumptive pulmonary TB (PTB) 16 to 24 weeks after enrollment. RESULTS: In total, 64 caregivers of 70 children (median age: 2y) with PTB completed the questionnaire. Most children (56%) had a known TB contact in the household. The questionnaire revealed that anticipated stigma was a common concern, with worries about people gossiping or speaking badly about their children (16.7%) or their child’s feelings being hurt because of their TB diagnosis (16.7%). Internalized stigma of the child, as perceived by their caregiver, was the least affirmed stigma domain. Overall, caregiver perceptions of internalized stigma did not delay treatment. Twelve of these caregivers were also interviewed, which demonstrated themes of anticipated and internalized stigma, and comparisons to HIV stigma. CONCLUSION: Deepening our understanding of stigma is critical to improving outcomes and experiences of young children and their families affected by TB.